Кон Janja Beč (Ed.), The Shattering of the Soul: Për Janja Beč (Ed.), The Shattering of the Soul - Vasilevska, Katerina; Ahmeti, Lindita (Identities: Journal for Politics, Gender and Culture, 2004)
Author(s): Katerina Vasilevska | Катерина Василевска Title (Macedonian): Кон Janja Beč (Ed.), The Shattering of the Soul Title (Albanian): Për Janja Beč (Ed.), The Shattering of the Soul Translated by (Macedonian to Albanian): Lindita Ahmeti Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 3, No. 1 (Summer 2004) Publisher: Research Center in Gender Studies - Skopje and Euro-Balkan Institute Page Range: 225-229 Page Count: 5 Citation (Macedonian): Катерина Василевска „Кон Janja Beč (Ed.), The Shattering of the Soul“, Идентитети: списание за политика, род и култура, т. 3, бр. 1 (лето 2004): Citation (Albanian): 225-229. Katerina Vasileska, „Për Janja Beč (Ed.), The Shattering of the Soul“, përkthim nga Maqedonishtja Lindita Ahmeti, Identities: Journal for Politics, Gender and Culture, Vol. 3, No. 1 (Summer 2004): 225-229.